2014
DOI: 10.1177/0884533614527773
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Enzyme Replacement Therapy During Pancreatic Insufficiency

Abstract: Pancreatic stimulation and therefore digestion is a tightly controlled and hormonally mediated process. Any alterations affecting any of the systematic steps for successful digestion and absorption to occur will impair appropriate pancreatic enzymatic secretion, entry into the bowel lumen, functionality once inside the lumen, and thus appropriate mixing with foods and nutrients. Many causes of pancreatic insufficiency may require the initiation of pancreatic enzyme therapy, including but not limited to cystic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 44 publications
0
83
0
3
Order By: Relevance
“…These recommendations encompass the main diseases associated with exocrine pancreatic insufficiency (like acute pancreatitis, chronic pancreatitis, pancreatic cancer, cystic fibrosis, celiac disease, irritable bowel syndrome, etc. ), defined as an inadequate pancreatic enzyme activity to digest food, generally due to either insufficient enzyme production, insufficient enzyme activation, or to early enzyme degradation [386, 392]. …”
Section: Resultsmentioning
confidence: 99%
“…These recommendations encompass the main diseases associated with exocrine pancreatic insufficiency (like acute pancreatitis, chronic pancreatitis, pancreatic cancer, cystic fibrosis, celiac disease, irritable bowel syndrome, etc. ), defined as an inadequate pancreatic enzyme activity to digest food, generally due to either insufficient enzyme production, insufficient enzyme activation, or to early enzyme degradation [386, 392]. …”
Section: Resultsmentioning
confidence: 99%
“…Data on gastric motility after non-TPIAT pancreatic surgery demonstrates delayed gastric emptying (DGE) in 45 to 50% of CP patients, and in 14 to 20% of post-pancreatectomy patients (58-62). An internal review at Johns Hopkins showed that 40% of patients experienced DGE post-TPIAT.…”
Section: Improving Outcomes After Total Pancreatectomymentioning
confidence: 99%
“…The pancreas plays an essential role in the digestion and absorption of nutrients (62, 63). CP may lead to malnutrition by multiple mechanisms, including malabsorption, decreased intake for fear of exacerbating pain, dietary restrictions, nausea, or gastric emptying problems.…”
Section: Improving Outcomes After Total Pancreatectomymentioning
confidence: 99%
“…5862 Data on gastric motility after non-TPIAT pancreatic surgery demonstrate delayed gastric emptying in 45% to 50% of patients with CP, and in 14% to 20% of patients after pancreatectomy. 5963 An internal review at Johns Hopkins showed that 40% of patients experienced delayed gastric emptying after TPIAT. Nausea, vomiting, poor oral intake, and constipation are common problems in both patients with CP and those after TPIAT.…”
Section: Improving Outcomes After Total Pancreatectomymentioning
confidence: 99%
“…63,64 CP may lead to malnutrition by multiple mechanisms, including malabsorption, decreased intake for fear of exacerbating pain, dietary restrictions, nausea, or gastric emptying problems. CP may lead to EPI.…”
Section: Improving Outcomes After Total Pancreatectomymentioning
confidence: 99%